2020
DOI: 10.1002/jsfa.10734
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate attenuated iE‐DAP induced inflammatory response in the mammary glands of dairy goats fed high‐concentrate diet

Abstract: BACKGROUNDLong‐term high‐concentrate (HC) diet feeding increased bacterial endotoxins, which translocated into the mammary glands of dairy goats and induced inflammatory response. γ‐d‐Glutamyl‐meso‐diaminopimelic acid (iE‐DAP), bacterial peptidoglycan component, triggered inflammatory response through activating nucleotide oligomerization domain protein 1 (NOD1) signaling pathway. While dietary supplemented with sodium butyrate (SB) relieved inflammatory response and improved animal health and production. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…There are several reasons. Firstly, sodium butyrate improved the rumen pH and comprehensively decreased the bacterial cell wall components (LPS, PGN and LTA) in rumen fluid and plasma, which was consistent with previous studies [ 10 , 14 , 15 ]. Sodium β -hydroxybutyrate also improved rumen pH, but to a less extent than sodium butyrate.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There are several reasons. Firstly, sodium butyrate improved the rumen pH and comprehensively decreased the bacterial cell wall components (LPS, PGN and LTA) in rumen fluid and plasma, which was consistent with previous studies [ 10 , 14 , 15 ]. Sodium β -hydroxybutyrate also improved rumen pH, but to a less extent than sodium butyrate.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, HC diet not only elevates LPS concentration in rumen fluid, but also results in a rise in plasma [ 1 , 2 ]. Several studies have suggested that HC diet also led to an increase of iE-DAP in the rumen and plasma [ 14 , 40 ]. In this present study, the HC diet significantly increased LPS concentration in plasma, which was in line with previous reports [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations